Bitter Legacy : Polish-American Relations in the Wake of World War II - Lukas, Richard C., 1937- (Book collections on Project MUSE., 1982)
In this most timely book, Richard C. Lukas offers the historical perspective that any reader, scholar, or layman needs to grasp the political turmoil in Poland in the decades after World War II. Bitter Legacy is the first major analysis of Polish-American relations from the Potsdam Conference through the Polish elections of 1947, the critical period during which Poland became a satellite in the Russian sphere. Drawing on an impressive array of primary and secondary sources, a number of which have never been used by scholars before, Lukas shows in detail why and how American policy was never a.